The Critical Role of Post-Harvest Handling in Vegetables - Neang Reachana; Mardy Serey (Jurnal Semesta Ilmu Manajemen dan Ekonomi, 2024)
The technological means of preventing crop loss after harvest is postharvest management and handling. One of the most crucial challenges for feeding the world's population sustainably in the future is reducing the loss and waste of various horticulture crops, as these losses can approach 50%. Vegetable handling and storage following harvest, processing procedures, distribution, and consumption are the main causes of post-harvest losses. The right post-harvest handling, packaging, shipping, and storage methods must be used in order to minimize post-harvest loss. This chapter includes the reasons behind the postharvest losses of several horticulture crops as well as workable ways to minimize these losses.